2021
DOI: 10.3390/foods10092104
|View full text |Cite
|
Sign up to set email alerts
|

Lactose Glycation of the Maillard-Type Impairs the Benefits of Caseinate Digest to the Weaned Rats for Intestinal Morphology and Serum Biochemistry

Abstract: The Maillard reaction between the lactose and milk proteins unavoidably occurs during the thermal treatment of milk. Although the impact of this reaction on protein nutrition and safety has been well-studied, whether a lactose glycation of milk proteins of the Maillard-type might affect the rats in their growth and intestinal morphology needs an investigation. In this study, caseinate and lactose-glycated caseinate were digested using pepsin and trypsin. Afterward, the resultant caseinate digest and glycated c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…It was also proven in the previous three studies of our group that casein lactose-glycation of Maillard-type was detrimental to the in vitro activities of the resultant casein hydrolysate, because this hydrolysate exerted a decreased barrier enhancement on IEC-6 cells [ 27 ], a lower growth proliferation and anti-apoptotic effect on IEC-6 cells [ 32 ], and a reduced immunomodulatory effect on the targeted immune cells [ 45 ]. Furthermore, the in vivo results from weaned rats also demonstrated that the casein lactose-glycation of the Maillard-type impaired the ability of casein hydrolysates to promote the development of small intestine and secretion of three digestive enzymes or three brush-border enzymes [ 46 ]. Our daily diets usually contain various products generated from Maillard reactions (especially AGEs).…”
Section: Discussionmentioning
confidence: 99%
“…It was also proven in the previous three studies of our group that casein lactose-glycation of Maillard-type was detrimental to the in vitro activities of the resultant casein hydrolysate, because this hydrolysate exerted a decreased barrier enhancement on IEC-6 cells [ 27 ], a lower growth proliferation and anti-apoptotic effect on IEC-6 cells [ 32 ], and a reduced immunomodulatory effect on the targeted immune cells [ 45 ]. Furthermore, the in vivo results from weaned rats also demonstrated that the casein lactose-glycation of the Maillard-type impaired the ability of casein hydrolysates to promote the development of small intestine and secretion of three digestive enzymes or three brush-border enzymes [ 46 ]. Our daily diets usually contain various products generated from Maillard reactions (especially AGEs).…”
Section: Discussionmentioning
confidence: 99%